The Evaluation of Smart City Policy in Bandung City - Siti Widharetno Mursalim (Program Pascasarjana Universitas Negeri Makassar, 2021)
Smart city is a smart city concept which in its implementation utilizes technology and information which greatly facilitates the public in accessing information. However, in implementing the Mayor's Regulation Number 1470 of 2018 concerning the Bandung Smart City Master Plan (the Bandung smart city master plan), problems were found in the roadmap which is part of the Bandung Smart City master plan for the 2018-2023 period. Given the smart city concept that continues to develop, an evaluation of smart city policies in the city of Bandung is carried out. This research was conducted using descriptive analysis by comparing the data that has been obtained, in which the results can be seen that the Bandung Smart City Master Plan already has a Roadmap containing program operations that will be carried out by the Implementing Regional Apparatus. However, the Roadmap contained in the Bandung Smart City Master Plan has not adjusted to changes in the implementation of Smart City in Bandung City including new programs that already exist, and there are no additional programs related to the dimensions of smart governance carried out by the Department of Communication and Information (Diskominfo) Bandung. This has resulted in a mismatch of programs and activities related to Smart City in the City of Bandung that have been or are being worked on.